A contingency model of the association between political turbulence, intensity of competition and balanced scorecard: impact on firm performance - Al-Naser, Khalis Hasan Yousif; Mohamed, Rapiah (2016)
Performance of manufacturing industry in Iraq has been declining over the last few decades. Worst still, many companies in the manufacturing sector in Iraq are yet to adopt Balanced Scorecard (BSC) to improve their performance despite its potency ensure to achieve competitive advantage and better performance.This study in view of this has conceptualized a framework that incorporates external factors of Political Turbulence and Intensity of Competition as predictors of Firm Performance through BSC. This paper is conceptual as its framework needs to be tested empirically by future researchers.